2009
DOI: 10.4049/jimmunol.0803253
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Growth Factor Improves Allogeneic Bone Marrow Engraftment through a CD4+Foxp3+ Regulatory T Cell-Dependent Mechanism

Abstract: Keratinocyte growth factor (KGF) protects mice from acute graft-vs-host disease and graft rejection by cytoprotective and yet incompletely understood immunological mechanisms. Recently, we showed that administration of KGF induces selective peripheral expansion of CD4+Foxp3+ regulatory T cells (Treg). In this study, we set out to assess whether the peripheral expansion of Treg accounts for the immunomodulatory effects of KGF after bone marrow (BM) transplantation. To exclude potentially confounding cytoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Even CD25 bright , which has been considered as a marker for identification of CD4 + Treg, may lead to confusing results in the cases of the tumor and autoimmune inflammatory diseases such as SLE because CD4 + Tregs defined by CD25 bright cannot be differentiated from activated effector T cells (20,21). Foxp3 has been proven to be a characteristic molecule related to the development and function of Treg (22,23). Foxp3 is also thought of as a relatively specific marker used in defining CD4 + Treg (6,11,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Even CD25 bright , which has been considered as a marker for identification of CD4 + Treg, may lead to confusing results in the cases of the tumor and autoimmune inflammatory diseases such as SLE because CD4 + Tregs defined by CD25 bright cannot be differentiated from activated effector T cells (20,21). Foxp3 has been proven to be a characteristic molecule related to the development and function of Treg (22,23). Foxp3 is also thought of as a relatively specific marker used in defining CD4 + Treg (6,11,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…As KGFR is expressed by several organs targeted by alloreactive T-cells, it was compelling to evaluate the effect of KGF in the setting of acute graft-versus-host disease (GVHD). In fact, current data have shown that KGF administration post-allogeneic BMT can: (i) facilitate alloengraftment [121], (ii) alleviate GVHD [122][123][124], (iii) protect epithelial cell in the gut mucosa while enhancing its repair [125], (iv) reduce the release of inflammatory cytokine [126], and (v) diminish allogeneic T-cell responses [121,127]. A subsequent study by Berent-Maoz et al further demonstrated that KGF not only protects TECs, but could also stimulate thymopoiesis indirectly by triggering them to secrete soluble factors [128].…”
Section: Kgf: To Guard the Thymic Epitheliummentioning
confidence: 99%
“…In addition to IL-2, other molecules inducing in vivo expansion of Tregs display a potential to improve engraftment, including keratinocyte growth factor (KGF). KGF facilitated engraftment in an MHC-matched HSCT murine model by increasing the frequency of Tregs and enhancing their in vivo immunosuppression ability ( 56 ). Importantly KGF lost its ability to improve engraftment in Scurfy mice that lack Tregs.…”
Section: Immunological Basis Of Graft Failurementioning
confidence: 99%